Training Effectiveness and Talent Development in Commercial Banks of Nepal - Dahal , Prabina (Journal of Kathmandu BernHardt College, 2025)
This research examines the influence of soft skills training on talent development within Nepal’s commercial banking sector, focusing on communication, leadership, teamwork, and problem-solving. These soft skills, alongside technical expertise, play a pivotal role in enhancing employability, organizational efficiency, and workforce adaptability. The study employs a mixed-methods explanatory sequential design, integrating quantitative and qualitative methods. The quantitative phase includes a sample of 384 employees from 21 commercial banks in Nepal, while the qualitative phase involves interviews with 16 trainers. Training effectiveness is assessed using the Four-Stage Cyclic Model and Kirkpatrick’s four-level model, which emphasize the importance of needs assessment, training design, and evaluation in improving employee performance. The study also explores training’s role in improving adaptability to technological advancements, particularly in enhancing digital skills. It further investigates challenges such as resource constraints, ineffective assessments, and the necessity for customized programs aligned with organizational and employee goals. Theoretical perspectives—including Talent-Based Theory, Expectancy Theory, Goal-Setting Theory, and Training Engagement Theory—offer insights into optimizing talent management and training effectiveness. Findings suggest that well-structured training substantially enhances soft skills, leading to improved career development and organizational success. However, the study identifies a gap in understanding the effectiveness of soft skills training within Nepal’s banking sector, stressing the need for future research to account for cultural, economic, and organizational factors. This study contributes to developing more tailored and effective training strategies to foster talent development in Nepal’s banking industry.